Prevention & Conservation: Historicizing the Stigma of Hearing Loss, 1910-1940. Issue 4 (December 2017) - Virdi, Jaipreet
During the early twentieth century, otologists began collaborating with organizers of the New York League for the Hard of Hearing to build a bridge to "adjust the economic ratio" of deafness and create new research avenues for alleviating or curing hearing loss. This collegiality not only defined the medical discourse surrounding hearing impairment, anchoring it in hearing tests and hearing aid prescription, but, in so doing, solidified the notion that deafness was a "problem" in dire need of a "solution." Public health campaigns thus became pivotal for spreading this message on local and national levels. This paper focuses on how, from the 1920s to 1950s, as otologists became more involved with social projects for the deaf and hard of hearing — advocating lip-reading, community work, and welfare programs — at the same time, they also mandated for greater therapeutic regulation, control of hearing aid distribution, and standardization of hearing tests. The seemingly paradoxical nature of their roles continued to reinforce the stigmatization of deafness: with widespread availability of effective help, the hearing impaired were expected to seek out therapeutic or technological measures rather than live with their affliction.